Research Progress of Safety Assessment Technology of Pressure Vessel Pipeline with Defects - Wu, Wan; Zhang, Ying; Huang, Guohong; Zhang, Hao (International Journal of Mechanical and Electrical Engineering, 2025)
Pressure vessel is widely used in the energy industry, military industry, scientific research and many other fields, the importance of its safe operation is self-evident, the safety of pressure vessel and pipeline has been an important research topic. For the safety assessment of defective vessels and pipelines, this paper firstly introduces the research results of the latest standards of defective equipment and pipelines, gives the latest progress of defect assessment theory, briefly reviews the application status of safety assessment of defective vessels, and finally proposes the current situation of domestic defect assessment, providing a basis for the safety evaluation of defective vessels and pipelines.